ANALISA PEMELIHARAAN ALAT INFUS PUMP DI RUMAH SAKIT UMUM SIBUHUAN - Sri Hariati Asmeri Harahap; Siti Rahmah (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2021)
An infusion pump is a very important tool to assist doctors in treating patients who are in treatment.Continous health care needs to be supported by equipment that is always in a ready to use condition and can function properly.Formulation of the problem: 1. How is the implementation of technical maintenance of the infusion pump in the hospital. 2. How the performance and repair of the infusion pump in the hospital. Objectives: 1. Todetermine the maintenance of the infusion pump in the hospital. 2. To find out the troubleshooting of the infusion pump.This research method is descriptive research type,aims to analyze the maintenance of the infusion pump and also to determine the results of the data obtained after observation and conclusion.The results of research conducted at the general hospital in the Sibuhuan area.This research,maintenance of the infusion pump was carried out in three stages of maintenance,namely: Monthly maintenance and quarterly maintenance and 6 monthly maintenance.The conclusion from the results of the discussion of research carried out on maintenance of the infusion pump can be concluded that the maintenance is carried out properly.